Dietary acid load and the odds of knee osteoarthritis: a case–control study - Soudabeh Hamedi-Shahraki; Jalal Moludi; Hawal Lateef Fateh; Farshad Amirkhizi (Scientific Reports)
Abstract Knee osteoarthritis (KOA) is a common form of arthritis that leads to joint pain and reduced mobility, especially among older adults. Recent studies indicate that dietary acid load (DAL) may play a role in the development of KOA by promoting systemic inflammation. This case-control study aims to investigate the relationship between DAL and KOA in adults aged 40 and older. A total of 150 newly diagnosed cases of KOA and 300 age-, sex-, and BMI-matched controls were recruited from Zabol County, Iran. Dietary intake was assessed using a validated food frequency questionnaire, and DAL was calculated based on nutrient content. Logistic regression was used to estimate the odds of KOA across DAL quartiles, adjusting for confounding factors such as physical activity, smoking, and supplement use. Individuals in the highest quartile of DAL had significantly higher odds of developing KOA compared to those in the lowest quartile (OR: 2.48, 95% CI: 1.36–4.51, p = 0.003), after adjusting for potential confounders. Additionally, the odds of developing KOA was found to increase with increasing quartiles of DAL in both male (OR: 2.52, 95%CI: 1.13 to 5.65, p = 0.024) and female (OR: 2.55, 95%CI: 1.06 to 6.31, p = 0.031) participants, after adjusting for potential confounding variables. This study demonstrates a significant association between high DAL and increased odds of KOA. Reducing DAL through dietary interventions may be a promising strategy for managing KOA, especially in aging populations. Further longitudinal studies are required to confirm these findings and explore causal relationships.